STUDY OF FMCW-BASED SYNTHETIC APERTURE RADAR AT L-BAND FREQUENCY AND ITS REALIZATION - ABIDIN (NIM: 23214323), ZAINAL
Synthetic Aperture Radar (SAR) is one of the imaging techniques that are widely used for mapping an area. SAR can work without the presence of sunlight in all weather conditions and has a large coverage area despite using a small antenna. There are some techniques to generate SAR signal, one of them is FMCW. This technique can detect any moving objects by transmitting relatively low transmit power as well as radar pulses. FMCW basically detects objects by comparing transmitted and received frequencies (beat frequency). Many researches have been done about SAR, however, those researches pay less attention to the dimensions of the SAR system. Therefore, this research aims to design an FMCW SAR that can be applied as a UAV payload. This research is divided into several stages; design, simulation, realization, and measurement. Designing stage aims to minimize the dimension system so it can be implemented as UAV payload, simulation aims to run the FMCW SAR design, and realization aims to integrate the blocks in the FMCW SAR design. The FMCW SAR is is designed to be built in L-band to detect trees and their branches. The output from each block FMCW SAR systems is then measured and compared to the output of the systems’s simulation. FMCW SAR that is built in this research has a maximum dimension of 300 mm × 450 mm × 55 mm (excluding antenna). To increase the maximum range detection, the system amplifies the signal both at transmitter and receiver. It was 17,3dB gain at transmitter and 16,68dB gain at receiver.